THE INFLUENCE OF AUDITOR PROFESSIONAL KNOWLEDGE AND SKILLS, SKEPTICISM, AUDIT DURATION TOWARD AUDIT QUALITY AHLIA CEMENT COMPANY/ALKHUMS - Abobakr Ali Alsdai (TEMA, 2023)
The aim of this research is to determine the influence of Auditor Professional Knowledge, Skepticism and Audit Duration on Audit Quality. This research is quantitative research that uses primary data sources from All Auditors in Libya. The power collection method used is a questionnaire. The data analysis technique used is the Statistical Package for the Social Sciences version 25. Based on the results of the analysis that has been carried out, it can be concluded that Auditor Professional Knowledge and Skills affect the Audit Quality, Skepticism affect the Audit Quality and Audit Duration affects Audit Quality. For Libyan government auditors, maintaining and enhancing audit quality is essential to ensure transparency, accountability, and the efficient use of public resources. Libyan government auditors can contribute to the improvement of audit quality and the overall governance of public sector entities in Libya.